The association of RBP4 with chronic kidney diseases in southern Chinese population - Chen, Tong; Liu, Yu; Wu, Shiquan; Long, Siyu; Feng, Ling; Lu, Wenqian; Chen, Wenya; Hong, Guoai; Zhou, Li; Wang, Fang; Luo, Yuechan; Zou, Hequn; et al. (Frontiers in Endocrinology, 2024)
Background Retinol binding protein 4 (RBP4), as a novel adipokine, has been proven to be highly related to insulin resistance, obesity, diabetes, hypertension, hyperuricemia and other metabolic diseases, which are all risk factors for chronic kidney disease (CKD). However, there is a lack of sufficient studies to explore the relationship between RBP4 and CKD, and no reports have described the predictive value of RBP4 for CKD. This study was designed to clarify the relationship between RBP4 and CKD and its potential predictive value. Methods Our team has conducted a large-scale cross-sectional survey that contained 2117 individuals on the southern coast of China. Correlation test, logistic regression analysis were used to evaluate the association between RBP4 and CKD. Receiver operating characteristic (ROC) were used to evaluate the optimal cut-off and predictive value of RBP4 for predicting CKD. Results By using the quartile grouping method, the population was divided into four groups according to the RBP4 level. As the RBP4 level increased, the prevalence of CKD also gradually increased among different groups. RBP4 was also correlated with various metabolic risk factors, such as blood glucose, blood lipids, blood pressure, waist circumference, uric acid, and with kidney function indicators such as creatinine, urine protein. Logistic regression analysis found that after adjusting for confounders, RBP4 remained significantly associated with CKD, independent of metabolic risk factors. ROC analysis showed that RBP4 as a single index, AUC (0.666) was superior to Scr, FBG, Log HOMA-IR, WC, TG, VLDL-C, UA, HDL-C, LDL-C, and that combining RBP4 indicator and other common risk factors of CKD can improve the accuracy for predicting CKD. Conclusion This study found that the RBP4 was strongly correlated with CKD, RBP4 may become a valuable marker and have strong power for predicting CKD.